Factors associated with Emergency Department revisits and hospitalization following discharged acute asthma exarcerbation - Nik Azlan Nik Muhamad; Kwong, LJ (Fakulti Perubatan, UKM, 2016)
The objectives were to identify factors associated with early revisit of adult patients with acute asthma exarcebation discharged from the Emergency Department (ED). It was a retrospective cohort study with patients aged 12 years or more within a period of 1 month and who were treated for acute asthma and discharged from the ED of Sarawak General Hospital. A total of 397 patients fulfilled sampling criteria and out of this number, 13.9% had revisit to the ED within 2 weeks. In all of these revisit cases, 9.1% were actually admitted. Prescription rate of oral corticosteroid was found to be low (24.9%) and abscond rate was high (25.1%). Patients who absconded from the ED and their concurrent infection were associated with early ED revisit.